Understanding the role of exogenous boosting in modeling varicella vaccination - Sandra E. Talbird; Elizabeth M. La; Josephine Mauskopf; Alexandra Altland; Vince Daniels; Lara J. Wolfson (Expert Review of Vaccines, 2018)
Introduction: The exogenous boosting (EB) hypothesis posits that cell-mediated immunity is boosted for individuals reexposed to varicella-zoster virus (VZV). Historically, mathematical models of the impact of universal childhood varicella vaccination (UVV) have used limited data to capture EB and often conclude that UVV will temporarily increase herpes zoster (HZ) incidence. Areas covered: We updated a 2013 systematic literature review of 40 studies to summarize new evidence from observational or modeling studies related to EB and its parameterization. We abstracted data on observational study designs and mathematical model structures, EB frameworks, and HZ-related parameter values. Expert commentary: This review identified an additional 41 studies: 22 observational and 19 modeling studies. Observational analyses generally reported pre-UVV increases in HZ incidence, making it difficult to attribute post-UVV increases to UVV versus other causes. Modeling studies considered a range of EB frameworks, from no boosting to full permanent immunity. Mathematical modeling efforts are needed in countries with long-standing vaccination programs to capture the dynamics of VZV transmission and temporal changes that may affect HZ incidence. Use of real-world pre-/postvaccination data on varicella and HZ incidence to validate model predictions may improve approaches to EB parameterization and understanding of the effects of varicella vaccination programs.